Pembiasaan Program Qailulah dalam Meningkatkan Disiplin Waktu Belajar di Era Digitalisasi Peserta Didik Kelas I SDIT Cahaya Fikri Bontang Tahun Pelajaran 2023/2024 - Novianti, Ameliani Nisa; Murni, Murni (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2024)
This research discusses the habituation of the Qailulah program with the main focus of research increasing the discipline in study time of class I students at SDIT Cahaya Fikri Bontang in the era of digitalization. The aim of this research is to find out how discipline in studying time can be improved in the era of digitalization through familiarizing students with the Qailulah program. Qailulah, known as napping, is the main discussion in this research. Lack of rest and no nap time for students will affect cognitive and affective abilities, including students disciplinary attitudes. This emphasizes the importance of getting used to the Qailulah program for students at school. The type of research used is qualitative. The data collection methods used were observation, interviews and documents, data analysis using data reduction, data presentation and drawing conclusions. Research is carried out directly. The research results show that familiarization with the Qailulah program can minimize excessive use of technology and make students more focused and emotionally stable so that their ability to discipline their study time can increase. Therefore, the Qailulah program can be a habit in disciplining the study time of class I students. In conclusion, the Qailulah program can improve the discipline of students' study time in the era of digitalization by using technology according to learning needs and requiring direct guidance from teachers and parents.